1979
DOI: 10.3382/ps.0580858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D3 and D3 Metabolites on Production Parameters and Hatchability of Eggs

Abstract: A two phase experiment was conducted with Leghorn pullets to study the effect of graded levels (0 to 18 Mg/kg feed) of vitamin D 3 , 25-OH-D 3 , l,25-(OH) 2 -D 3 , and la-OH-D 3 on production parameters and hatchability of eggs. Phase 1 was conducted with 21-week-old pullets for a period of 13 weeks. There were 10 treatments with four replicates of 10 hens in each cage. Eggs were incubated weekly for a period of 8 weeks beginning when the hens were 26 weeks of age. Another phase of the experiment was started w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
2
6
1
1
Order By: Relevance
“…The lack of improved performance agrees with some previous reports (Roland and Harms, 1976;Abdulrahim et al, 1979;Harms et al, 1988). However, the data in the present paper do not agree with other reports published previously (Charles and Ernst, 1974;Sunde, 1975;Mc-Loughlin and Soares, 1976;Polin and Ringer, 1977;Soares, 1979;Hamilton, 1980;Soares et al, 1988).…”
Section: Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…The lack of improved performance agrees with some previous reports (Roland and Harms, 1976;Abdulrahim et al, 1979;Harms et al, 1988). However, the data in the present paper do not agree with other reports published previously (Charles and Ernst, 1974;Sunde, 1975;Mc-Loughlin and Soares, 1976;Polin and Ringer, 1977;Soares, 1979;Hamilton, 1980;Soares et al, 1988).…”
Section: Methodscontrasting
confidence: 59%
“…Several workers reported that adding a vitamin-D metabolite to the feed improved eggshell quality (Charles and Ernst, 1974;Sunde, 1975;McLoughlin and Soares, 1976;Polin and Ringer, 1977;Soares, 1979;Hamilton, 1980;Soares et al, 1988). However, other workers found no improvement in eggshell quality from the addition of vitamin D metabolites to the diet (Roland and Harms, 1976;Abdulrahim et al, 1979;Harms et al, 'Florida Agricultural Experiment Station, Journal Series Number 9641. 1988).…”
Section: Introductionmentioning
confidence: 92%
“…However, 'Scientific Article Number A-4590, Contribution Number 7586 of the Maryland Agricultural Experiment Station, Department of Poultry Science. Abdulrahim et al (1979) found no effect of la-OH-D 3 or l,25(OH) 2 D 3 on egg shell weight when fed to young hens. Bar and coworkers (Bar et al, 1984;Bar and Hurwitz, 1987) have shown that plasma l,25(OH) 2 D 3 was greater in laying hens with good egg shell quality and was reduced with age.…”
Section: Introductionmentioning
confidence: 79%
“…Although it has been previously reported that egg shell quality can be improved by feeding 25-hydroxycholecalciferol (25-OH-D 3 ) instead of cholecalciferol to laying hens (Charles and Ernest, 1974;Sunde, 1975;Roland and Harms, 1976;McLoughlin and Soares, 1976;Polin and Ringer 1977;Abdulrahim et al, 1979;Hamilton, 1980), the effectiveness of 25-OH-D 3 is controversial. Relatively few studies have evaluated the effects of the more active 1 hydroxylated vitamin D metabolites on egg shell quality.…”
Section: Introductionmentioning
confidence: 97%
“…However, the eggshell quality was determined in only six hens per treatment group. In a much larger study, Abdulrahim et al (1979) found no effect on eggshell quality in young laying hens fed 3 or 9 ug l,25-(OH)2D3/kg diet; at the higher dose, feed consumption decreased significantly and egg production decreased slightly. Addition of relatively low levels (1.5 to 4.5 ug/kg) of l,25-(OH) 2 D 3 to a normal layer diet containing cholecalciferol either had no effect or reduced feed consumption, egg weight (EW), and egg production Harms et al, 1988).…”
Section: Introductionmentioning
confidence: 84%